Pseudomonas syringae Type III Secretion Protein HrpP Manipulates Plant Immunity To Promote Infection - Ya Jin; Wei Zhang; Shen Cong; Qi-Guo Zhuang; Yi-Lin Gu; Yi-Nan Ma; Melanie J. Filiatrault; Jun-Zhou Li; Hai-Lei Wei (Microbiology Spectrum, 2023)
ABSTRACT The bacterial plant pathogen Pseudomonas syringae deploys a type III secretion system (T3SS) to deliver effector proteins into plant cells to facilitate infection, for which many effectors have been characterized for their interactions. However, few T3SS Hrp (hypersensitive response and pathogenicity) proteins from the T3SS secretion apparatus have been studied for their direct interactions with plants. Here, we show that the P. syringae pv. tomato DC3000 T3SS protein HrpP induces host cell death, suppresses pattern-triggered immunity (PTI), and restores the effector translocation ability of the hrpP mutant. The hrpP-transgenic Arabidopsis lines exhibited decreased PTI responses to flg22 and elf18 and enhanced disease susceptibility to P. syringae pv. tomato DC3000. Transcriptome analysis reveals that HrpP sensing activates salicylic acid (SA) signaling while suppressing jasmonic acid (JA) signaling, which correlates with increased SA accumulation and decreased JA biosynthesis. Both yeast two-hybrid and bimolecular fluorescence complementation assays show that HrpP interacts with mitogen-activated protein kinase kinase 2 (MKK2) on the plant membrane and in the nucleus. The HrpP truncation HrpP1–119, rather than HrpP1–101, retains the ability to interact with MKK2 and suppress PTI in plants. In contrast, HrpP1–101 continues to cause cell death and electrolyte leakage. MKK2 silencing compromises SA signaling but has no effect on cell death caused by HrpP. Overall, our work highlights that the P. syringae T3SS protein HrpP facilitates effector translocation and manipulates plant immunity to facilitate bacterial infection. IMPORTANCE The T3SS is required for the virulence of many Gram-negative bacterial pathogens of plants and animals. This study focuses on the sensing and function of the T3SS protein HrpP during plant interactions. Our findings show that HrpP and its N-terminal truncation HrpP1–119 can interact with MKK2, promote effector translocation, and manipulate plant immunity to facilitate bacterial infection, highlighting the P. syringae T3SS component involved in the fine-tuning of plant immunity.